Consumer Choice in Residential Mortgage Market: An Islamic Mortgage Contract. Issue 4 (14th December 2021) - Azmat, Uzair; Azmat, Saad; Hassan, M. Kabir; Ali, Syed Zahid
Abstract: This paper examines the Islamic mortgage contract of Diminishing Musharakah and its impact on consumer welfare, house purchase, and mortgage payments. We build both static and dynamic models to study a homeowner's decision-making. We pay special attention to expectation formations and simulate the model to analyze both Islamic and Conventional mortgage holders' responses to changes in income growth, house prices, and interest rates. Estimates of the model, using housing data set of U.S. economy (1990–2018), indicate that Diminishing Musharakah contract holders achieve 2.5 to 4% higher discounted utility under constant and declining learning expectations. The reducing balance feature of the Diminishing Musharakah contract provides relative protection to a consumer from adverse income shocks and high-interest rate environments. Simulation results suggest that under dynamic conditions, the Diminishing Mushrakah provides 3.4% lower mortgage cost per housing unit. It prevents consumers of average and low-risk appetite from relatively riskier housing decisions. We learn that consumer chooses a 2.5% smaller house size under Diminishing Musharakah. The model also examines consumers with vector autoregressive (VAR) based expectations. We find that homeowners with optimistic forecasts may achieve a higher utility in a conventional mortgage.